The main challenges affecting the performance of small and medium-sized enterprises (SMEs): Case study of the SME Roadmap of Azerbaijan - Akhundova, Narmin (ADA University, 2020)
Small and medium-sized enterprises (SMEs) are important drivers for the health and sustainability of the economies. They are the primary source of productivity growth and job creation. The paper intends to find out the main challenges affecting the performance of SMEs and to what extent the SME Roadmap is being implemented in Azerbaijan. To achieve the goal, the study researches on the theory of “Business environment” and its limits, SME’s opportunities and challenges in a global context, especially in the European Union (EU) and Eastern Partnership (EaP) countries (in the example of Georgia). The study further analyses the current trends in the economic diversification strategy of Azerbaijan, its success and challenges, and influencing factors for the performance of SMEs in Azerbaijan, as well as evaluation of the short-term objectives of the SME Roadmap. The research design of the study is cross-sectional using a mixed approach: both qualitative and quantitative research methods. The primary data was collected through structured interviews and quantitative survey questionnaires among small-scale survey sample. The study used secondary data from the publications of various institutions through online sources. The study concludes that there are three main challenges affecting the performance of SMEs, which are limited access to finance and lack of skilled employees, and regulation, namely tax inspections and illegal demands by law enforcement bodies. While analyzing the short-term achievements of the Strategic Roadmap, the study completes that the implementation is limited with the establishment of different state bodies, associations and centers. This research is inductive and expressive in nature. The researcher formed a model based on research findings, which could be statistically measured in the future.
Keywords: Business; Business Environment -- Azerbaijan.; Entrepreneurship -- Azerbaijan.; Eastern partnership -- Azerbaijan.; Azerbaijan -- Economic conditions -- 1991-; Azerbaijan -- Economic policy.; Azerbaijan -- Foreign relations -- 1991-